The context of COVID-19 affected the long-term sleep quality of older adults more than SARS-CoV-2 infection - Peixoto, Vanessa Giffoni M. N. P.; Facci, Lucas Alves; Barbalho, Thiago C. S.; Souza, Raíssa Nascimento; Duarte, Alice Mendes; Almondes, Katie Moraes (Frontiers in Psychiatry, 2024)
Introduction: Sleep problems are one of the most persistent symptoms of post-COVID syndrome in adults. However, most recent research on sleep quality has relied on the impact of the pandemic, with scarcely any data for older adults on the long-term consequences of COVID infection. This study aims to understand whether older individuals present persistently impaired sleep quality after COVID-19 infection and possible moderators for this outcome. Methods: This is a cross-sectional analysis of a longitudinal cohort study with 70 elders with 6-month-previous SARS-CoV-2 infection and 153 controls. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality; Geriatric Depression Scale and Geriatric Anxiety Inventory for screening depression and anxiety. Demographics and comorbid conditions were collected. Results: The mean age of participants was 66,97±4,64 years. There were no statistical differences in depression and anxiety between groups. Poor sleep quality was found in 52,9% and 43,8% of the COVID and control groups (p=.208). After controlling for multiple variables, all the following factors resulted in greater chances of poor sleep quality: female gender (OR, 2.12; p=.027), memory complaints (